Graduates' perceptions of competencies and preparation for labour market transition. The effect of gender and work experience during higher education - Monteiro, Sílvia (2016)
Purpose - The purpose of this paper is to explore the influence of work experience and gender on graduates' perception of competencies, preparation and expectations of success in labour market (LM) transition. The research questions that guide this study are: How do graduates evaluate the competencies acquired during their masters' degree? How do graduates evaluate their preparation for transition to the LM and their expectations of success?Design/methodology/approach - Within the framework of employability models, the authors explore the perception of competencies developed during higher education (HE). Given previous reported effects of gender and work experience on the process of work transition, these two variables are also considered. A questionnaire was administered to 411 students in their final masters' degree year. Descriptive and inferential statistics, namely, univariate analysis of variance (F-anova 2 x 3) with post-hoc multiple comparison test (post-hoc HSD of Tukey), are developed to analyse the data and address the research questions.Findings - The main results show that there are no significant group differences concerning perception of the development of competencies; the effect of work experience on perceptions related to preparation for transition to the LM depends on gender; and expectations of successful transition to the LM are related to gender, with no significant influence of prior work experience.Originality/value - These data suggest that, in developing their programmes, it is important for HE institutions to consider self-beliefs related to students' diversity, in order to maximize the development and effective use of competencies and individual resources in work contexts, for all students. Exploration of the effect of gender and work experience on perceptions of competencies and preparation for the LM should help HE institutions define curricular programmes and support graduates in preparing for entry to the LM.